Ergonomic Risk Assessments of Timber Harvesting Workers in Teak Plantations, Phrae Province - ณ ตะกั่วทุ่ง ชาคริต; ดิลกสัมพันธ์ ปิยวัตน์ (Thai Journal of Science and Technology, 2021)
The study of the ergonomic risk assessments of timber harvesting workers in teak plantations, Phrae province was aimed at assessing the ergonomic risks of the work posture of teak workers to improve safety and health of workers. The study was carried out in four teak plantations. Work postures were assessed by using REBA and RULA techniques, and analyzed using descriptive statistics. The results of the study showed that most of REBA risk assessments had a moderate (action level 2) (81.25%) risk value, meaning investigations and possible work changes were required. The majority of RULA risk assessments were at a high (action level 3) (56.25%) risk value, meaning investigations were required, as well as possible quickly work changes. Tasks that need urgent improvement consisted of the mahout, crane choker setting, tractor choker setting, log number marking, cutting to length, and tree feller. The works could be improved by adjusting the posture to minimize the stooping of the torso as much as possible. Additional tools such as chainsaw hooker, increase the length of the chainsaw bar, or modify the design of the chainsaw could be applied to keep the cutting posture in a straight back position. If there is an adequate budget, the modern machinery may be used in the timber harvesting work.